Longitudinal assessment of [18F]FDG‐PET in the TgF344‐AD rat. (December 2021) - da Rocha, Andreia Silva; Ferreira, Pamela C.L.; Bellaver, Bruna; Peixoto, Guilherme G. Schu; Venturin, Gianina Teribele; Greggio, Samuel; da Costa, Jaderson Costa; Souza, Diogo O.; Zimmer, Eduardo R.
Abstract: Background: The development and characterization of biomarkers abnormalities in Alzheimer's disease (AD) animal models is particularly important for the investigation of pathophysiological mechanisms and drug development. With this is mind, here, we aimed at characterizing the brain glucose metabolism, indexed by [ 18 F]FDG‐microPET, of the TgF344‐AD rat, a model harboring human APP/PS1 mutations. We hypothesized early hypometabolism ‐ due to astrocyte reactivity and microglial activation ‐ followed by hypometabolism in later stages – due to neurodegeneration. Method: Hemizygous TgF344‐AD rats and their sex‐matched wild type littermates (n=16) were evaluated in three time points: 3, 6 and 9 months of age. Rats underwent [ 18 F]FDG‐microPET for brain glucose metabolism analysis (SUVr, using the pons as reference region). Locomotor activity and spatial memory were assessed using Open‐Field and and Y‐maze tests, respectively. Result: TgF344‐AD animals showed no differences in [ 18 F]FDG‐microPET analysis in any of the ages analyzed (Figure A). On the other hand, a decline on their performance in the Y‐maze task was identified at the 9 months time point (p = 0.0132), suggesting a decline in their spatial memory at this age (Figure B). No differences were identified on the parameters analyzed in the Open Field task. Conclusion: This study is the first to investigate the in vivo brain glucose metabolism in the TgF344‐AD rat model. Our preliminary results suggest that, in comparison to age and sex‐matched littermates, this APP/PS1 rat model does not present relevant changes in the brain glucose metabolism at early stages, even in the presence of detectable cognitive decline.